Pengembangan Tata Kelola Teknologi Informasi Berbasis E-Administrasi Di Perguruan Tinggi (Studi Kasus LPTK FKIP Universitas Lampung) - Amarulloh - Universitas Lampung (Indonesian Journal of Networking and Security (IJNS), 2015)
Abstract: Development of Information Technology Governance Based E-Administration in Higher Education (Case Study in LPTK of FKIP Lampung University). The quality of public services both in the aspect of administrative services, services of goods and services is still not optimal so in order to overcome these problems, the effort done was by utilizing information technology systems. The development of e-administration as the use of information technology (such as internet, telephone and satellite) and information systems by the institution aimed to improve agency performance in relation to society, the business community, and other related groups. Implementation of e-administration will create the culture Information Technology (IT) which was the responsibility of each sub/units within the faculty (Self Responsibility). The method used was the Research and Development (R & D). The results showed that with the implementation of information technology systems based e-administration, it created service excellence, that was effectiveness and efficiency of work, data accuracy, up to date data, as well as optimum service to all stakeholders. Accelerating of Information and Communication Technology (ICT) development in the Faculty which has goal of network development autonomy, can also serve as a competence development media, as well as a learning laboratory.Keywords: E-Administration, Database, Excellent Service Abstrak: Pengembangan Tata Kelola Teknologi Informasi Berbasis E-Administrasi Di Perguruan Tinggi (Studi Kasus LPTK FKIP Universitas Lampung) Kualitas pelayanan publik baik pada aspek pelayanan administratif, pelayanan barang maupun jasa masih belum optimal sehingga untuk mengatasi permasalahan tersebut upaya yang dilakukan adalah dengan memanfaatkan sistem teknologi informasi. Pengembangan e-administrasi sebagai pemanfaatan teknologi informasi (seperti internet, telepon dan satelit) dan sistem informasi oleh institusi bertujuan untuk meningkatkan kinerja instansi dalam hubungannya dengan masyarakat, komunitas bisnis, dan kelompok terkait lainnya. Penerapan e-administrasi akan menciptakan culture Technology Information (TI) yang menjadi tanggung jawab di masing-masing sub/unit yang ada di fakultas (Self Responsibility). Metode penelitian yang digunakan adalah Penelitian dan Pengembangan (R&D). Hasil penelitian menunjukkan bahwa dengan diterapkannya sistem teknologi informasi berbasis e-administrasi, tercipta pelayanan yang prima yakni, efektifitas dan efisiensi pekerjaan, akurasi data, data yang up to date, serta pelayanan yang optimal kepada seluruh stakeholder. Akselerasi pengembangan Teknologi Informasi dan Komunikasi (TIK) Fakultas yang memiliki tujuan otonomi pengembangan jaringan, juga dapat berfungsi sebagai media pengembangan kompetensi, sekaligus sebagai laboratorium pembelajaran.Kata kunci: E-Administrasi, Data Base, Pelayanan Prima